Pengaruh Risiko Kredit, Kualitas Manajemen, Ukuran Perusahaan, Likuiditas dan Solvabilitas Terhadap Kinerja Keuangan Perbankan Konvensional Yang Terdaftar di BEI Tahun 2019-2022 - Fadil, Muhammad; Arifin, Rois; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to examine the effect of Credit Risk, Management Quality, Firm Size, Liquidity and Solvency on Financial Performance with Return On Asset (ROA) as a measure of financial performance in the conventional banking sector listed on the Indonesia Stock Exchange (IDX). This study uses the population of all conventional banks registered on the Indonesia Stock Exchange (IDX) during the period 2019-2022 with a sample of 23 companies. The results of the study show that Net Interest Margin (NIM) and Firm Size have a positive and significant effect on Financial Performance measured by ROA, while Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) and Debt to Equity Ratio (DER) have a negative and significant effect on financial performance measured by ROA Keywords: Return On Asset (ROA), Non Performing Loan (NPL), Net Interest Margin (NIM), Firm Size, Loan to Deposit Ratio (LDR), Debt to Equity Ratio (DER).